Toward a real liquid biopsy in metastatic breast and prostate cancer: Diagnostic LeukApheresis increases CTC yields in a European prospective multicenter study (CTCTrap). Issue 10 (19th September 2018) - Andree, Kiki C.; Mentink, Anouk; Zeune, Leonie L.; Terstappen, Leon W.M.M.; Stoecklein, Nikolas H.; Neves, Rui P.; Driemel, Christiane; Lampignano, Rita; Yang, Liwen; Neubauer, Hans; Fehm, Tanja; Fischer, Johannes C.; et al.
Abstract : Frequently, the number of circulating tumor cells (CTC) isolated in 7.5 mL of blood is too small to reliably determine tumor heterogeneity and to be representative as a "liquid biopsy". In the EU FP7 program CTCTrap, we aimed to validate and optimize the recently introduced Diagnostic LeukApheresis (DLA) to screen liters of blood. Here we present the results obtained from 34 metastatic cancer patients subjected to DLA in the participating institutions. About 7.5 mL blood processed with CellSearch® was used as "gold standard" reference. DLAs were obtained from 22 metastatic prostate and 12 metastatic breast cancer patients at four different institutions without any noticeable side effects. DLA samples were prepared and processed with different analysis techniques. Processing DLA using CellSearch resulted in a 0–32 fold increase in CTC yield compared to processing 7.5 mL blood. Filtration of DLA through 5 μm pores microsieves was accompanied by large CTC losses. Leukocyte depletion of 18 mL followed by CellSearch yielded an increase of the number of CTC but a relative decrease in yield (37%) versus CellSearch DLA. In four out of seven patients with 0 CTC detected in 7.5 mL of blood, CTC were detected in DLA (range 1–4 CTC). The CTC obtained through DLA enables molecular characterization of the tumor. CTC enrichment technologies however still need to be improved to isolate all the CTC present in the DLA. Abstract : What's new? Circulating tumor cells (CTC) can mirror tumor heterogeneity but a standard blood sample (7.5 mL) is too small to truly represent the tumor. To increase the yield of CTC, the authors used Diagnostic LeukApheresis in which liters of blood are screened for the presence of CTC in metastatic cancer patients. They report a significant increase in CTC yield and consequently, a better molecular characterization of the tumor, encouraging further research into the use of leukapheresis as "liquid biopsy" in cancer patients.